Characterization of the vertical evolution of the three-dimensional turbulence for fatigue design of tidal turbines. (21st August 2020) - Thiébaut, Maxime; Filipot, Jean-François; Maisondieu, Christophe; Damblans, Guillaume; Jochum, Christian; Kilcher, Levi F.; Guillou, Sylvain
Abstract : A system of two coupled four-beam acoustic Doppler current profilers was used to collect turbulence measurements over a 36-h period at a highly energetic tidal energy site in Alderney Race. This system enables the evaluation of the six components of the Reynolds stress tensor throughout a large proportion of the water column. The present study provides mean vertical profiles of the velocity, the turbulence intensity and the integral lengthscale along the streamwise, spanwise and vertical direction of the tidal current. Based on our results and considering a tidal-stream energy convertor (TEC) aligned with the current main direction, the main elements of turbulence prone to affect the structure (material fatigue) and to alter power generation would likely be: (i) the streamwise turbulence intensity ( I x ), (ii) the shear stress, v ′ w ′ ¯, (iii) the normal stress, u ′ 2 ¯ and (iv) the vertical integral lengthscale ( L z ). The streamwise turbulence intensity, ( I x ), was found to be higher than that estimated at other tidal energy sites across the world for similar height above bottom. Along the vertical direction, the length ( L z ) of the large-scale turbulence eddies was found to be equivalent to the rotor diameter of the TEC Sabella D10. It is considered that the turbulence metrics presented in this paper will be valuable for TECs designers, helping them optimize their designs as well as improve loading prediction through the lifetime of the machines. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.